Neural evidence for competition-mediated suppression in the perception of a single object. (November 2015) - Cacciamani, Laura; Scalf, Paige E.; Peterson, Mary A.
Abstract: Multiple objects compete for representation in visual cortex. Competition may also underlie the perception of a single object. Computational models implement object perception as competition between units on opposite sides of a border. The border is assigned to the winning side, which is perceived as an object (or "figure"), whereas the other side is perceived as a shapeless ground. Behavioral experiments suggest that the ground is inhibited to a degree that depends on the extent to which it competed for object status, and that this inhibition is relayed to low-level brain areas. Here, we used fMRI to assess activation for ground regions of task-irrelevant novel silhouettes presented in the left or right visual field (LVF or RVF) while participants performed a difficult task at fixation. Silhouettes were designed so that the insides would win the competition for object status. The outsides (grounds) suggested portions of familiar objects in half of the silhouettes and novel objects in the other half. Because matches to object memories affect the competition, these two types of silhouettes operationalized, respectively, high competition and low competition from the grounds. The results showed that activation corresponding to ground regions was reduced for high - versus  low-competition silhouettes in V4, where receptive fields (RFs) are large enough to encompass the familiar objects in the grounds, and in V1/V2, where RFs are much smaller. These results support a theory of object perception involving competition-mediated ground suppression and feedback from higher to lower levels. This pattern of results was observed in the left hemisphere (RVF), but not in the right hemisphere (LVF). One explanation of the lateralized findings is that task-irrelevant silhouettes in the RVF captured attention, allowing us to observe these effects, whereas those in the LVF did not. Experiment 2 provided preliminary behavioral evidence consistent with this possibility.